Quality in Business Process Modeling - Krogstie, John (Springer International Publishing : Imprint: Springer, 2016)
This book covers the whole spectrum of modeling goals to achieve optimal quality in the process model developed. It focuses on how to balance quality considerations across all semiotic levels when models are used for different purposes, and is based on SEQUAL, a framework for understanding the quality of models and modeling languages, which can take into account all main aspects relating to the quality of models. Chapter 1 focuses on the theoretical foundations, introducing readers to the topics of business processes and business process modeling, as well as the most important concept underlying the modeling of business processes. In turn, Chapter 2 addresses the quality of models in general and business process models in particular. Chapter 3 contains a specialization of SEQUAL for quality of business process models. In Chapter 4, examples of the practical uses of business process models are provided, together with the results of detailed case studies on how to achieve and maintain quality in business process models. Chapter 5 presents a process modeling value framework that demonstrates how to achieve more long-term and higher return on investment with regard to (business) process and enterprise models. Lastly, Chapter 6 reviews the main points of the book and discusses the potential for business process modeling in the future through its combination with other types of modeling. The book has two intended audiences. It is primarily intended for computer science, software engineering and information system students at the postgraduate level who want to know more about business process modeling and the quality of models in preparation for professional practice. The second audience consists of professionals with extensive experience in and responsibilities related to the development and evolution of process-oriented information systems and information systems methodologies in general, who need to formalize and structure their practical experience or update their knowledge as a way to improve their professional activity. The book also includes a number of real-world case studies that make it easier to grasp the main theoretical concepts, helping readers apply the approaches described.